Improving parenting and healthy nutrition for stunted toddler mothers through community service programs - Lamria Situmeang; Rida Millati; Tridamayanty Syamsul; Indrawati Aris Tyarini; Ari Setiawati; Yefta Primasari (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2024)
Stunting is a significant public health problem, especially among toddlers, caused by chronic malnutrition and suboptimal parenting. This community service program aims to overcome these problems by providing relevant education and interventions to mothers of toddlers who experience stunting. This program aims to improve the knowledge and skills of mothers under five in terms of parenting and healthy nutrition, as well as encourage behavioral changes that support optimal child growth and development. This program is carried out through a series of educational activities, including training on balanced nutrition, how to serve nutritious food, and parenting techniques that support children's health. In addition, this activity also involves direct counseling and the provision of educational materials that are easy to understand by mothers of toddlers. The evaluation was carried out to measure the improvement of parenting knowledge, skills, and practices and their impact on the nutritional status of children. Early results showed a significant increase in maternal knowledge about the importance of balanced nutrition and healthy parenting. Practical skills in the presentation of nutritious food have also improved. Further evaluation showed that there was an improvement in the nutritional status of toddlers and a decrease in the prevalence of stunting in the target community. This community service program has succeeded in improving parenting and healthy nutrition knowledge for mothers of stunted toddlers. This intervention is expected to be a model for similar programs in other regions and make a positive contribution to reducing stunting rates more broadly